Redshift/Blueshift by Chris Mansell - Merry, Bruce (LiNQ (Literature in North Queensland), 2016)
Bruce Merry reviews: Chris Mansell, Redshift/Blueshift, Five Islands Press, Wollongong, 1988, 64pp., 8.95.